Aglutenic cupcakes for gastro-intestinal symptoms and hematological indices in diagnosed celiac children –A randomized trialWhat is knownWhat is new - Shaista Jabeen; Azmat Ullah Khan (Clinical Nutrition Open Science)
S U M M A R Y: Fundamental adherence to gluten-free diet can improve gastrointestinal symptoms. Substitution of wheat should be done in order to fulfil gluten-free criteria and nutrient density. Objective: This study was conducted to assess the efficacy of gluten free cupcakes formulated by substitution of low FODMAP foods. Design: Random parallel assignment was adopted (1b). Methods: A 12 weeks efficacy trial was conducted on children of age 3–8 years, and were randomly allocated into two groups (n = 35 in each group). Gluten free cupcakes group was provided with gluten-free flour blend cupcakes (35 g), while placebo group was provided with rice flour-based cupcakes. Results: Weight was significantly increased in both placebo (13.7 ± 4.8 to 14.5 ± 4.4) and gluten free (13.6 ± 4.6 to 15.4 ± 4.6) groups. Mid upper arm circumference was significantly increased in gluten free group only (15.3 ± 3 to 15.5 ± 3). Abdominal pain was reduced to 38.7% from 6.5% (absent) in the placebo group compared to gluten free group 15.2%–33.3% (absent), while diarrhea was reduced to 33.3% from 27.3%. Serum platelets were significantly reduced in gluten free cupcake group (GFC) from 308.4 ± 39.5 to 300.3 ± 38.7 (P < 0.05). Tissue trans-glutaminase antibody (tTg-IgA) was significantly reduced from 148 ± 51 to 127 ± 31. Conclusion: Formulated gluten-free cupcakes are found to be effective in improving gastrointestinal symptoms and anthropometrics in patients with celiac disease. ClinicalTrials.gov PRS: Record Summary NCT06359613.